2005
DOI: 10.4319/lo.2005.50.6.1908
|View full text |Cite
|
Sign up to set email alerts
|

Domoic acid: The synergy of iron, copper, and the toxicity of diatoms

Abstract: Diatom blooms generated by the alleviation of iron limitation in high nitrate-low chlorophyll (HNLC) regions of the oceans often are composed of pennate diatoms of the genus Pseudo-nitzschia, many of which periodically produce the potent neurotoxin domoic acid. We show that toxigenic diatoms have an inducible high-affinity iron uptake capability that enables them to grow efficiently on iron complexed by strong organic ligands in seawater. This low-iron adaptive strategy requires copper and domoic acid, a coppe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
191
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 177 publications
(198 citation statements)
references
References 35 publications
6
191
1
Order By: Relevance
“…The physiological role of DA was further documented in Maldonado et al (2002) and Wells et al (2005). Maldonado et al (2002) reported that DA production was inversely related to cellular growth rates when cells were limited by low iron or copper availabilities.…”
Section: The Ecological Role Of Da Productionmentioning
confidence: 97%
See 2 more Smart Citations
“…The physiological role of DA was further documented in Maldonado et al (2002) and Wells et al (2005). Maldonado et al (2002) reported that DA production was inversely related to cellular growth rates when cells were limited by low iron or copper availabilities.…”
Section: The Ecological Role Of Da Productionmentioning
confidence: 97%
“…Bates et al, 1989;Martin et al, 1990;Fryxell et al, 1997;Gallacher et al, 2001). It is known that DA leaks, or is actively transported, out of the cells, resulting in high levels of the toxin in the surrounding medium (reviewed by Bates, 1998;Wells et al, 2005). It is therefore reasonable to speculate that this toxin could have an allelopathic effect.…”
Section: Allelopathymentioning
confidence: 99%
See 1 more Smart Citation
“…Iron colimitations and interactions with other nutrients and trace metals have been observed (e.g. Schulz et al, 2004;Mills et al, 2004;Wu et al, 2003;Wells et al, 2005) and apparently the composition of trace metals and macro nutrients greatly affect natural Fe fertilization efficiency (see Sect. 2.2).…”
Section: Iron and Climate Changementioning
confidence: 99%
“…Once overlooked and neglected (Wells, 1998), progress has been made in understanding the nature and importance of organic colloidal material in seawater and coastal systems and challenged the simple discrimination into particulate and dissolved iron (0.45 or 0.2 µm filtered). Furthermore, dynamic exchange between larger iron particles, colloidal iron, and soluble iron (defined as passing either a 0.02 µm or a 1 kDa filter) also directs interest towards the particulate and soluble phase.…”
Section: Colloidal Iron and Organic Mattermentioning
confidence: 99%